An empirical study on the post divorce enforcement of court orders in civil court - Mohd Zin, Najibah; Abdul Hak, Nora; Che Soh @ Yusoff, Roslina; Md Hashim, Noraini; Ibrahim, Kamilia; Md Said, Muhamad Helmi; Ambaras Khan, Hanna; Mohd Noor, Nadiah; Ahmad Fuzi, Fauziah Hani (2018)
This study examines problems on the enforcement of court orders of the Civil Courts in Malaysia. Despite the fact that civil courts are guided by comprehensive statutory laws, issues on matters related to the enforcement orders especially maintenance orders are still unresolved. Therefore this study is undertaken to examine and identify problems that have caused the failure to enforce the orders of post-divorce issues. The sample consists of one hundred and sixty-seven respondents came from five regions in Malaysia. A survey-using questionnaire was the main method of collecting the data. To support the empirical evidence, the semi-structured interview has also been conducted in this study. The study discloses an obvious co-relation between complex and lengthy processes, unnecessary time consuming and costs inefficiency with the enforcement order of post-divorce issues. This article is a preamble to an envisaged study on the enforcement of the order in the Civil Court of which the result will be useful for further improvement of the existing legal provisions in Malaysia.